Kreasi berbagai macam kue tradisional Bugis Makassar - Nurfaizah A. P; Srikandi Srikandi; Riny Jefri (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
This Devotion to Society intend to improve the skill of Housewives on creating various kinds of Bugis-Makassar traditional cake, and also construct independency in entrepreneurship. Some benefits obtained from this activity include (1) Obtain knowledge about Bugis-Makassar traditional cake, (2) Improving skill of creating traditional cake especially Barongko, Jompo-Jompo, and Kue Lapis, (3) Obtain knowledge about enterpreneurhip. This activity was done on Friday and Saturday 23rd-24th of August 2019 with the number of participants are 10 people. Training program led by lecturers with assistance from students of Welfare Family Education. Training method used are presentation, demonstration and practice. Devotion to Society activity could be done as plan because: 1) Good cooperation between Practitioner Team and Village Working Unit on location, 2) Participation of all participants, 3) Strategic location to develop production, 4) Availability of raw materials for product development, and 5) Strategic location for marketing expansion. The conclusion from the result of Devotion to Society Activity is in the Excellent Category.